Antiplatelet therapy in acute coronary syndrome. Issue 1 (March 2017) - Brown, A. J. M.; Austin, D.
Abstract: Antiplatelet therapy is an essential component in the treatment of acute coronary syndromes (ACS). ACS management has evolved significantly over recent years with new antiplatelet agents with distinct pharmacological properties that offer a faster onset of action and greater potency. Prospective randomized controlled trials have not only focused on reducing ischemic events, but also on complications. There is a tipping point with safety/efficacy, beyond which bleeding risk can outweigh any anti‐ischemic benefit. This tipping point is not fixed and estimating its position for an individual patient remains a major challenge and is critically influenced by a multitude of factors including age and comorbidity. The European Society of Cardiology (ESC) guidelines provide important direction to the trainee and practicing cardiologist. This article outlines development in antiplatelet therapy focusing on mechanism of action, the evolution in the evidence‐base, clinical indications, and clinical controversies. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5222689/Activity.aspx